Thermodynamic study of the adsorption of Cd2+ and Ni2+ onto chitosan – Silica hybrid aerogel from aqueous solution - Kelechi Ebisike; Afamefuna Elvis Okoronkwo; Kenneth Kanayo Alaneme; Ojo Jeremiah Akinribide (Results in Chemistry, 2023)
Adsorption studies have been conducted on aqueous solution to investigate the effect of temperature on the sorption of Cd2+ and Ni2+ by Chitosan-silica hybrid aerogel [(CS)hA], which was developed using a blend of components from crab exoskeleton and bamboo biomass and synthesized using sol–gel method. The application of this derived aerogel for clean-up of water bodies polluted with heavy metals at varying temperatures was undertaken with a view to establish its effectiveness. The studied temperatures were 301 K, 308 K, 318 K, 328 K and 338 K at pH 3 and contact time of 180 mins and 60 mins for Cd2+ and Ni2+, respectively. Data obtained were subjected to Langmuir, Freundlich, Temkin and Dubinin–Radushkevich isotherm models which were used to evaluate the adsorption process. Langmuir Isotherm model proved to be the best fit in interpreting the adsorption process with the maximum Cd2+ sorption values within 57.14 to 57.80 mg g−1 while Ni2+ sorption values lie between 52.08 and 58.82 mg g−1. The effect of enthalpy (ΔH°), entropy (ΔS°) and Gibbs free energy (ΔG°) on the sorption of Cd2+ and Ni2+ by the derived aerogel were also deduced. The process is spontaneous, exothermic with the studied ions well aligned on the derived aerogel surface.